Desenvolvimento de um flash multifásico na presença de hidratos - Sirino, Thales Henrique (2017)
Gas hydrates are crystalline compounds formed by hydrogen-bonded water frameworks. Hydrates are stabilized by non-polar molecules of low molecular diameters (guest molecules), which are occluded in cavities (host lattice) of the crystalline structure formed by water molecules. The interaction between the host and guest molecules occurs by van der Waals forces. The formation of gas hydrates depends on temperature, pressure and gas composition. Some practical situations that favor the formation of hydrates are the operations involving multiphase flow of water, oil and natural gas under favorable thermodynamic conditions, a scenario commonly found in the oil industry.The formation and agglomeration of hydrates can cause blockage of transmission lines oil and / or gas, reducing process efficiency, damaging the equipment and compromise the safety of the operating part. In this study, a new robust flash algorithm was developed and implemented for equilibrium calculation in systems with clathrate hydrates. Were performed calculations of vapor-liquid equilibrium, gas solubility in liquids and hydrate equilibrium in the liquid-hydrate-vapor region, as well as above the upper quadrupole point (liquid-liquid-hydrate) and below the lower quadrupole point (ice-hydrate-vapor). The systems analyzed encompass complex multicomponent mixtures (hydrocarbons, carbon dioxide, nitrogen), including mixtures of thermodynamic inhibitors of different chemical nature (salts, alcohols, glycols). For the prediction of hydrate formation conditions a thermodynamic model was implemented based on the van der Waals and Platteeuw ideal solid theory. The model is based on the equality of chemical potentials of all species in all phases. For the equilibrium calculations of the other phases, the Cubic-Plus-Association (CPA) state equation was used. The results obtained with the present model were compared with the literature data and with the CSMGem software. A good agreement with the experimental data was observed, demonstrating the reliability of the methodology used.